Transformasi Gen Pembungaan melalui Agrobacterium tumefaciens Secara In-Vitro pada Tanaman Anggrek Vanda tricolor - DWIYANI, RINDANG; YUSWANTI, HESTIN; MERCURIANI, IXORA SARTIKA; SEMIARTI, ENDANG (Agrotrop : Journal on Agriculture Science; Vol 6 No 1 (2016), 2017)
In Vitro Transformation of Flowering Gene through Agrobacterium tumefaciens on Vandatricolor Orchid. Research concerning of Agrobacterium-mediated transformation of Vanda tricolor orchid had been done during March to August 2014. Objectives of this research wasto investigate the effects of period of inoculation with Agrobacterium suspension and application of acetosyringone (AS) on the percentage of transforman candidates. The T-DNA harbored the PaFT gene under the control of promoter of Ubiquitin and the hpt gene, ahygromycine resistant gene as a selectable marker for transformant selection. This T-DNA was constructed in the PGAS vector and transferred to the plant genome mediated by A. tumefaciens. The period of inoculation with Agrobacterium and application ofAcetosyringone (AS) were trialed in this research. The result showed that a period of one hour inoculation with Agrobacterium suspension added with 25 ppm AS resulted in the highest number of transforman candidates. i.e. 7.04% compared to 4.10% (one hour inoculation without AS), 3.76% (two hours inoculation without AS), and 4.48% (two hours inoculation with 25 ppm AS).
Keywords: Agrobacterium tumefaciens; acetosyringone; PaFT gene; period of inoculation; Vanda tricolor orchid